2003
DOI: 10.1046/j.1365-2249.2003.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of Th1 responses and CD154 expression in human CD4+ T cells by IFN-α

Abstract: SUMMARYLike interleukin (IL)-12, interferon (IFN)-a has been shown to play an important role in inducing human Th1 responses. Recent studies have shown that human Th1 responses driven by IL-12 are associated with enhanced expression of CD154. The present study examined the effects of IFN-a on CD154 expression in human CD4 + T cells, with special attention to the relationship with Th1 responses. Highly purified CD4 + T cells from healthy donors were stimulated with immobilized anti-CD3 with or without IFN-a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
(33 reference statements)
2
20
0
Order By: Relevance
“…Thus, IL-12 has been shown to increase the IFN-c production of activated CD4? T cells [19]. Of note, in the present study, anti-IL-12 monoclonal antibodies almost completely abrogated the anti-P-mediated upregulation of the IFN-c production of PBMC, indicating that the enhancement of IFN-c production of PBMC by anti-P requires the presence of IL-12 produced by monocytes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, IL-12 has been shown to increase the IFN-c production of activated CD4? T cells [19]. Of note, in the present study, anti-IL-12 monoclonal antibodies almost completely abrogated the anti-P-mediated upregulation of the IFN-c production of PBMC, indicating that the enhancement of IFN-c production of PBMC by anti-P requires the presence of IL-12 produced by monocytes.…”
Section: Discussionmentioning
confidence: 66%
“…Autoantibodies to ribosomal P proteins (anti-P) are detected in 12-16% of patients with SLE [1]. Anti-P are directed to 3 phosphoproteins (P0, P1, and P2), which are located on the larger 60S subunit of eukaryotic ribosomes, and have molecular weights of 38,19, and 17 kDa, respectively [1]. Anti-P have been shown to react a common linear determinant that is present in the carboxyl-terminal 22-amino acid sequence [1].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] We have recently revealed that IFN-a by itself did not enhance IFN-g production or mRNA expression in anti-CD3-stimulated human CD4 1 T cells in the absence of accessory cells or exogenous IL-12. 18 Consistently, IFN-a enhanced IL-12 receptor b2 (IL-12Rb2) mRNA expression in CD4 1 T cells. 18 It is therefore indicated that the induction of human T H 1 responses by IFN-a requires the presence of IL-12.…”
mentioning
confidence: 84%
“…NM 005012) and ␤ -actin -specific primers as described [28] . PCR products were finally visualized by running agarose gel (1.5%) electrophoresis containing ethidium bromide.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%